The Role of Social Support and Mindfulness on The Posttraumatic Growth of Young Adults Surviving Childhood Maltreatment - Ettah, Nurul Aini Adinda; Soetikno, Naomi; Dewi, Fransisca Iriani Roesmala (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Recent research has found that negative experiences due to childhood maltreatment do not always persist; survivors can experience positive growth, which is called posttraumatic growth (PTG). Two of the protective factors that encourage PTG are social support and mindfulness. Social support through empathy, giving new perspectives, and appreciation can help survivors deal effectively with traumatic events and lead to the PTG process. In addition, survivors who have mindfulness can also practice direct involvement with their thoughts and feelings, not judge traumatic events, and help survivors rebuild the meaning of the world. This correlational and quantitative study examined the role of social support and mindfulness in posttraumatic growth (PTG) among 114 young adult survivors of childhood maltreatment aged 20–40 years (M = 24.84, SD = 4.55). The measuring tools used in this study were the Posttraumatic Growth Inventory—Short Form (PTG-SF), the Multidimensional Scale of Perceived Social Support (MSPSS), the Tarumanagara Five-Facet Mindfulness Questionnaire (TFFMQ), and the Childhood Trauma Questionnaire—Short Form (CTQ-SF). Using multiple regression analysis, results showed that social support (β = 0.350 p < 0.01) and mindfulness (β = 0.336 p < 0.01) had a positive effect on PTG in young adults who survived childhood maltreatment, with the higher support and mindfulness felt by the survivors, the higher the PTG they experienced. This research shows the importance of social support and mindfulness in shaping positive changes in the lives of young adults who have survived childhood maltreatment.